Effect of crop residues applied isolated or in combination on the germination and seedling growth of horse purslane (Trianthema portulacastrum) - Khaliq,A. (2011)
Soil incorporation of crop residues can lead to weed suppression by posing allelopathic and physical effects. Allelopathic potential of the crops sorghum, sunflower, brassica applied as sole or in combination for horse purslane (Trianthema portulacastrum) suppression was evaluated in a pot investigation. Chopped crop residues alone and in combination were incorporated at 6 g kg-1 soil (12 t ha-1), and a weedy check was maintained. Germination traits time to start germination; time to 50% emergence, mean emergence time, emergence index and final germination percentage were negatively influenced by residue incorporation. Crop residues also exerted a pronounced negative influence on the shoot and root length of horse purslane. Significant suppression in leaf and root score and leaf area per plant was also observed. A combination of sorghum and sunflower residues accounted for maximum (71%) seedling mortality. Soil incorporation of allelopathic crop residues can be employed for horse purslane management.